An Analysis of the Digital Transformation-Based Learning Implementation System in the Era of Disruption - Adrianus Nabung; Laurentius Ni; Ambros Leonangung Edu (Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this paper is to complete the shortcomings of previous studies related to the challenges of implementing learning in the current era of disruption. In an effort to find alternative solutions that are more effective, this study seeks to analyze and examine how educators transform themselves to face various challenges in education in accordance with the spirit of the times. The existence of educational disruption has not been followed by an emphasis on the importance of digital-based transformative education and strengthening the competence of educators as an increasingly ideal basis for transformation. This paper is based on the argument that no matter how strong the influence of the pace of development of digital information technology, which tends to be disruptive, the spillover of which has shaken the education sector, creative and dynamic efforts will increasingly find momentum during the Covid-19 pandemic. Thus, educators continue to play a vital role in the educational process that cannot simply be replaced by technological sophistication. Within the limits of this understanding, basically all achievements of scientific and technological progress are rooted in the educational process by placing the basis of digital transformation as a starting point for change to a better, civilized and quality direction.